2017
DOI: 10.11114/jets.v5i9.2536
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Attitude towards Teaching Profession: Mediating Role of Self Efficacy

Abstract: The objective of the present study is to examine the correlation between the five factor personality traits of pre-service teachers and their attitudes towards the teaching profession and to test the mediating role of the pre-service teachers' self-efficacy beliefs. The study population included pre-service teachers that attended the "pedagogical formation course" instructed / applied in İnönü University, Faculty of Education, Department of Educational Sciences in 2015-2016 academic year. The survey sample inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
11
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
7
11
1
3
Order By: Relevance
“…The findings further reveal that there is no relationship between pre-service teachers' teaching self-efficacy and personality factors, namely neuroticism (N) and extraversion (E) ( Table 5). These findings are contrary to previous findings (Djigic, Stojiljov and Doskovic 2013;Jamil et al 2012;Senler and Sungur-Vural 2013;Ustuna 2017), which reported a significant positive relationship between extraversion and teacher self-efficacy belief. These findings are also in contrast with the findings of other studies (Jamil et al 2012; Tze 2014; Senler and Sungur-Vural 2013; Ustuna 2017), which established a negative association between neuroticism and self-efficacy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings further reveal that there is no relationship between pre-service teachers' teaching self-efficacy and personality factors, namely neuroticism (N) and extraversion (E) ( Table 5). These findings are contrary to previous findings (Djigic, Stojiljov and Doskovic 2013;Jamil et al 2012;Senler and Sungur-Vural 2013;Ustuna 2017), which reported a significant positive relationship between extraversion and teacher self-efficacy belief. These findings are also in contrast with the findings of other studies (Jamil et al 2012; Tze 2014; Senler and Sungur-Vural 2013; Ustuna 2017), which established a negative association between neuroticism and self-efficacy.…”
Section: Discussioncontrasting
confidence: 99%
“…Few studies that have investigated the relationship between teaching self-efficacy and preservice teachers' personality traits, observed that there was a significant positive relationship between extraversion and teacher self-efficacy beliefs (Djigic, Stojiljov and Doskovic 2013;Jamil, Downer and Pianta 2012;Senler and Sungur-Vural 2013;Ustuna 2017). Conversely, neuroticism was found to be negatively associated with self-efficacy (Jamil et al 2012;Klassen and Tze 2014;Senler and Sungur-Vural 2013;Ustuna 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Attitudes play a vital role because they can impact teachers' practices. It is also known that attitude is significantly related to efficacy (Çaycı, 2011;Demirtaş et al, 2011;Mahajna, 2014;Üstüner, 2017). Zero-order correlation coefficients showed that gender had relationships with both teacher efficacy beliefs and attitudes toward teaching.…”
Section: Discussionmentioning
confidence: 96%
“…Results show that participant student teachers have a high level of efficacy beliefs and a medium level of attitude toward teaching. High level of teacher efficacy is a common finding in the literature (Aydin & Woolfolk Hoy, 2005;Tschannen-Moran & Hoy, 2007;Üstüner, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Personality traits influence the choice of role which in turn shape the direction of behaviour (Legkauskas, 2008). It has been determined that personality traits are associated with the carrier related decisions and the self-efficacy (Tomšik & Gatial, 2018;Üstüner, 2017), the involvement with the professional activity (Wang et al, 2006) and the leadership in the school environment (Marshall et al, 2012). Teachers' personality traits are reflected in their satisfaction with the job (Paleksić el al., 2017), their performance at work (Rusbadrol et al, 2015;Pourghaz, Jenaabadi, & Ghaeninejad, 2016), efficiency of learning (Fatemi et al, 2015), subjective wellbeing, and the academic achievement of students (Eryilmaz, 2014).…”
Section: Vocational Teachers' Personality Traitsmentioning
confidence: 99%